Validation of the Korean translation of obesity-related problems scale assessing the quality of life in obese Korean - Lee, Yeon Ji (The Korean Surgical Society, 2013)
PURPOSE: The objective of this study was to translate the obesity-related problems (OP) scale for Koreans and to validate it for use in Korean populations. METHODS: Translation and back-translation of the OP scale was performed and a pilot test was conducted. Following this, patients who had received treatment at the Obesity Center of Inha University Hospital were selected for participation in the field test. Cronbach's alpha (α) was used for assessment of the internal consistency of the OP scale. Spearman's correlation coefficients were used to assess the concurrent validity between the OP scale, the EuroQoL-5D (EQ-5D), and the Beck depression inventory (BDI) scale. One-way analysis of variance and t-test were used to assess the factors associated with the OP scale. RESULTS: A total of 67 individuals participated in the field study. The standardized Cronbach's α of the OP was 0.913. A significant negative correlation was observed between the OP scale and the EQ-5D and a positive correlation was observed between the OP scale and the BDI (the correlation coefficient with EQ-5D = -0.316, and the BDI = 0.305, P < 0.05). CONCLUSION: The results of this study prove that the Korean version of the OP has been translated and adapted correctly in order to meet the standard of its use.